COLLABORATIVE LEARNING IN THE 21ST CENTURY TEACHING AND LEARNING LANDSCAPE: EFFECTS TO STUDENTS’ COGNITIVE, AFFECTIVE AND PSYCHOMOTOR DIMENSIONS - Sotto, Romeo Jr Beriso (International Journal of Educational Management and Innovation, 2021)
Collaborative Learning (CL) is an approach to teaching and learning that involves a group of learners working together. The study aims to assess collaborative learning effects in the 21st-century teaching-learning landscape, particularly on the students' cognitive, affective and psychomotor dimensions. This study utilized the descriptive-evaluative method of research with a validated questionnaire as the primary data gathering instrument. Results showed that females dominate male students as to their number in first and second-year levels. The majority of the respondents aged 20 and below have participated in various collaborative activities and assignments in and out of the class with a typical size of 5 to 7 group members. Collaborative learning found to have a very high effect on Students' Academic Learning (cognitive), Collaborative Skills (affective) and least on Skills development (psychomotor). The researchers recommend that male students be engaged in group dynamics and learning activities; it must involve teenagers and suffice their activities' preference. Activities that demand greater participation, drills and exercises, and thinking activities must allow the students to develop their cognitive, affective, and psychomotor dimensions for holistic learning.